2011
DOI: 10.1016/j.icarus.2011.08.010
|View full text |Cite
|
Sign up to set email alerts
|

A layer of ozone detected in the nightside upper atmosphere of Venus

Abstract: International audienceTo date, ozone has only been identified in the atmospheres of Earth and Mars. This study reports the first detection of ozone in the atmosphere of Venus by the SPICAV ultraviolet instrument onboard the Venus Express spacecraft. Venusian ozone is characterized by a vertically confined and horizontally variable layer residing in the thermosphere at a mean altitude of 100 km, with local concentrations of the order of 107-108 molecules.cm-3. The observed ozone concentrations are consistent wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
54
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 88 publications
(58 citation statements)
references
References 24 publications
3
54
1
Order By: Relevance
“…This one-dimensional photochemical model involves 61 reactions and 24 species and was specifically adapted to the Venus nightside. As discussed by Montmessin et al (2011), the observed ozone peak density is significantly less than the modelled 3.9x10 9 cm -3 , probably because the chlorine mixing ratio was underestimated in the photochemical model. Also, one-dimensional models do not consider the global circulation of the atmosphere, which is however very important to correctly reproduce density distributions (Brecht et al, 2011(Brecht et al, , 2012.…”
Section: Density Profilesmentioning
confidence: 85%
See 4 more Smart Citations
“…This one-dimensional photochemical model involves 61 reactions and 24 species and was specifically adapted to the Venus nightside. As discussed by Montmessin et al (2011), the observed ozone peak density is significantly less than the modelled 3.9x10 9 cm -3 , probably because the chlorine mixing ratio was underestimated in the photochemical model. Also, one-dimensional models do not consider the global circulation of the atmosphere, which is however very important to correctly reproduce density distributions (Brecht et al, 2011(Brecht et al, , 2012.…”
Section: Density Profilesmentioning
confidence: 85%
“…The CO 2 density profile was derived from stellar occultations with the SPICAV instrument. Similarly, the ozone peak density is based on the recent SPICAV detections of an ozone layer near 110 km by Montmessin et al (2011). The O vertical distribution is obtained from the analysis of the O 2 (a 1 ∆) emission at 1.27 μm observed with the VIRTIS instrument.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations